Factors influencing health literacy among undergraduates in northeast Thailand: A cross-sectional study: 10.55131/jphd/2026/240212 - Ladda Pholputta,; Orathai Pongkaew,; Sutthisak Noradee,; Toemjai, Thawatchai (Journal of Public Health and Development, 2026)
To enable enlightened health decisions and sustain overall well-being, health literacy (HL) is fundamental. For university students in Thailand, HL influences lifestyle choices, healthcare access, and academic performance. The purpose of this research was to evaluate the variables linked to HL among university students. To guarantee sufficient statistical power, a descriptive cross-sectional study including 559 students was performed, and the sample size was established using power analysis. Data collection included a personal information form and a health literacy questionnaire based on the "3A2S" framework, covering six dimensions including health knowledge, information access, communication, decision-making, behavior modification, and information sharing. High reliability (Cronbach's alpha = 0.97) was exhibited by the questionnaire. The findings revealed significant associations between HL levels and gender, academic department, underlying disease status, and GPA (p < 0.05). Those in the nursing department (p = 0.035) and students with a GPA ≥3.0 (p < 0.001) were more prone to exhibit higher levels of HL, as revealed by multiple logistic regression analysis. These findings highlight the necessity for targeted measures, such as customized educational programs and seminars, to improve health literacy among students, especially those pursuing non-health-related disciplines. Future studies should develop and evaluate such programs to support informed health practices within academic communities.